Mutational Landscape of CEBPA in Mexican Pediatric Acute Myeloid Leukemia Patients: Prognostic Implications - Molina Garay, Carolina; Carrillo Sánchez, Karol; Flores Lagunes, Luis Leonardo; Jiménez Olivares, Marco; Muñoz Rivas, Anallely; Villegas Torres, Beatríz Eugenia; Flores Aguilar, Hilario; Núñez Enríquez, Juan Carlos; Jiménez Hernández, Elva; Bekker Méndez, Vilma Carolina; Torres Nava, José Refugio; Flores Lujano, Janet; et al. (Frontiers in Pediatrics, 2022)
Background In Mexico, the incidence of acute myeloid leukemia (AML) has increased in the last few years. Mortality is higher than in developed countries, even though the same chemotherapy protocols are used. CCAAT Enhancer Binding Protein Alpha (CEBPA) mutations are recurrent in AML, influence prognosis, and help to define treatment strategies. CEBPA mutational profiles and their clinical implications have not been evaluated in Mexican pediatric AML patients. Aim of the Study To identify the mutational landscape of the CEBPA gene in pediatric patients with de novo AML and assess its influence on clinical features and overall survival (OS). Materials and Methods DNA was extracted from bone marrow aspirates at diagnosis. Targeted massive parallel sequencing of CEBPA was performed in 80 patients. Results CEBPA was mutated in 12.5% (10/80) of patients. Frameshifts at the N-terminal region were the most common mutations 57.14% (8/14). CEBPA biallelic (CEBPABI) mutations were identified in five patients. M2 subtype was the most common in CEBPA positive patients (CEBPAPOS) (p = 0.009); 50% of the CEBPAPOS patients had a WBC count > 100,000 at diagnosis (p = 0.004). OS > 1 year was significantly better in CEBPA negative (CEBPANEG) patients (p = 0.0001). CEBPAPOS patients (either bi- or monoallelic) had a significantly lower OS (p = 0.002). Concurrent mutations in FLT3, CSF3R, and WT1 genes were found in CEBPAPOS individuals. Their contribution to poor OS cannot be ruled out. Conclusion CEBPA mutational profiles in Mexican pediatric AML patients and their clinical implications were evaluated for the first time. The frequency of CEBPAPOS was in the range reported for pediatric AML (4.5–15%). CEBPA mutations showed a negative impact on OS as opposed to the results of other studies.